Zero Waste Strategy for a Green Campus - Gislaine Ap. Moreira; Emilia Wanda Rutkoskwi (Universitas Diponegoro, 2021)
When adopting the zero waste strategy for the implementation of waste management measures at a Higher Education Institution, the commitment in the institution is of fundamental importance, not only with solid waste, but with the sustainability issue under a circular economy perspective, which should gradually be incorporated to the different programs and routine actions from universities. Several directions can be taken in the construction of this path so that universities are managed under the sustainability’s premises. In this article, the zero waste strategy for implementation of a circular economy program will be analyzed as a way to consolidate the process Green Campus. A qualitative and exploratory research was undertaken on green campus and zero waste strategies, mainly in universities. Although there is still a limited number of universities committed to zero waste actions, it was possible to appoint the benefits when implementing institutional programs related to sustainability and the fulfillment of the Sustainable Development Goals.